Integration of Ethnoscience in STEAM-Based Physics Learning to Enhance High School Students’ Scientific Literacy and 21st-Century Skills - Rosynanda Nur Fauziah; Ali Sunandar; Andri Suryana; Hasbullah (Jurnal Pendidikan Fisika, 2025)
Physics learning at the senior high school (SMA) level still largely focuses on cognitive aspects and formula memorization, making it difficult for students to connect scientific concepts with real-life situations and local cultural contexts. This study aims to describe the forms of ethnoscience integration in STEAM-based (Science, Technology, Engineering, Art, and Mathematics) Physics learning and to analyze its contribution to enhancing students’ scientific literacy and developing their 21st-century skills. This research employed a qualitative approach with a descriptive–exploratory design and was conducted at a public senior high school (SMA Negeri) in Subang Regency, West Java. Data were collected through participatory observation, in-depth interviews, and documentation, then analyzed thematically using the Miles and Huberman (2014) model with source and method triangulation. The findings revealed that ethnoscience integration was implemented through the use of local cultural phenomena—such as pottery making, traditional waterwheels, and simple irrigation systems—as contexts for STEAM-based project learning in Physics. The integration effectively facilitated the development of students’ scientific literacy, strengthened higher-order thinking skills, and fostered collaborative and communicative attitudes. In conclusion, STEAM-based Physics learning integrated with ethnoscience serves as an effective pedagogical innovation that bridges science and culture, enhances scientific literacy, and nurtures students’ character to become culturally grounded individuals who are well-prepared to face the challenges of the 21st century.